The Concept of Indefeasible Title in Electronic Land Certificates as an Initiative to Prevent Land Mafia - Weningtyas, Annisa; Subekti, Rahayu; Raharjo, Purwono Sungkowo (Indonesian Academy of Social and Religious Research (IASRR), 2024)
The study aims to analyze the indefeasible title concept on electronic land certificates for preventing land mafia. This research is normative legal research using legal and conceptual approaches. Legal materials include primary and secondary legal materials. According to the study, one of the causes of the land mafia is the land registration system's tendency to publish harmful material, as contained in Government Regulation 24 of 1997 on Land Registration. Therefore, reforming and developing the land law system into a positive publication system is necessary. By the Regulations of the Minister of Agrarian No. 1 of 2021 on Electronic Certificates, Electronic certificates are expected to be a database of landlords to reduce land disputes and strengthen the legitimacy of land certificates as a guarantee of ownership of land rights in Indonesia. Suppose an error in the registration procedure of a positive publication causes the losses of the party that should be more entitled. In that case, the state will guarantee compensation in substance to the party whose right is proven correct using the indefeasible title concept.